Risk-based decision making and the calibration of structural design codes – prospects and challenges. Issue 1 (2nd January 2019) - Köhler, Jochen; Baravalle, Michele
ABSTRACT: To date, our built environment is broadly developed and maintained on the basis of structural design standards. Most design standards contain simplified semi-probabilistic safety concepts that help daily structural engineering decision making using simple calculus. For few projects, the semi-probabilistic safety concept is replaced by advanced probabilistic methods that allow for reliability-based design. Neither include explicit consideration of optimality criteria. However, for the development and the calibration of the semi-probabilistic and probabilistic safety concepts it is important that societal preferences in regard to risk acceptance and the optimal use of natural resources are explicitly considered. In the present contribution, the development and calibration of semi-probabilistic and probabilistic structural design standards is represented as a formal decision problem allowing an optimal combination of reliability elements to be identified.